Occupancy estimation using environmental parameters - Wan, Shirley (2017)
Heating, ventilation, and air conditioning (HVAC) systems are the biggest energy consumer in office building. This has become a major problem as large amount of energy is wasted which contributes to global warming and greenhouse gas emission. Thus, saving energy has become very important, especially for countries like Singapore which have quite limited resources.